“Today the Pot is Boiling Over!”: Ebony Magazine, the Black Revolts, and the Search for a Social Resolution, 1966-1967 - Sid Ahmed Ziane (European Journal of American Studies)
This paper argues for Ebony’s effective intervention during the Black revolts that swept the U.S between 1966 and 1967. While Ebony was a glossy magazine designed for promoting Black fashion, advertising, and consumerism, it also proved to be a critical outlet aiming at bringing about a social reformation to Black America. At the time when the popular and the regional White and Black-owned media did not provide a practical resolution to the race riots whilst others generated instances of sensationalism to vilify the Black revolt, Ebony appeared as a sui generis magazine by providing viable social resolutions to quell the Black revolts and the social problems impinging upon Black Americans. This intervention was culminated in a special issue which critically addressed the Black youth and their rationale behind sparking off the revolts. Its intervention, however, paid off, with the National Advisory Commission on Civil Disorders approaching the magazine to procure copies to use them on its investigation of the riots while inviting its senior editor Lerone Bennett Jr. to participate in its close meetings on the civil disorder. Based on archival materials as well as Ebony’s special issues, this article sheds new light on Ebony’s social standing in Post-war America.